Léčba závislosti na tabáku - zlepšení dostupnosti v klinické praxi - Králíková, Eva (Casopis lekaru ceskych, 2012)
Tobacco dependence is a disease that causes dozens of illnesses and premature deaths. Effective treatment exists and should be available to all smokers in frame of the local health care service. The Czech Republic is not the only country missing the full availability. A worldwide project "Global Bridges: Healthcare Alliance for Tobacco Dependence Treatment" is trying to improve the situation. As we can see from the website globalbridges.org, the project focuses on different geographical regions of the world - even if comparisons between countries are difficult due to the different health care systems including their financing. The European Globalbridges group met in June 2012 in Birmingham at the occasion of the UK National Smoking Cessation Conference. The entire interconnected system of thousands of people involved in smoking cessation in UK, including research support, is truly impressive and may be an example to other countries not only in Europe.
Keywords: poruchy vyvolané užíváním tabáku; Smoking Cessation; Humans; Tobacco Use Disorder; lidé; odvykání kouření